Dynamic Virtual Programming Optimizing the Risk on Operating System - Prashant Kumar Patra; Padma Lochan Pradhan (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
This virtual programming language is a primary method of improving the performance and protecting system resources in around the clock on anywhere and anytime platform. This proposed article is contributes to the development of an optimal method that aims  to determine the minimal cost and time to be invested into secure and robust computing in right way, right time. everywhere and everytime of the globe. Furthermore, the virtual programming method optimizing the (CPU, MEMORY) space & time of the operating system. This dynamic code fully support to the current virtualization to co-op with large scale complex infrastructure and applications. We have to define, design, develop & deployment the virtual programming ( C++, JAVA & RAIN ) on real time operating system to participates the millions of users able to access on line web and mobile application  simultaneously. We have to integrate this VPL with real time hardware, software and middleware to facilitate to customers requirement. This dynamic code is communicating, interfacing, message passing, replicating among the several subjects and objects over a distributed super scalar environment (MIMD). This proposed method optimized the system attacks and down time by implementing VPL on complex heterogonous infrastructure.